The Role of Economic Policy in Achieving Economic Diversification in Libya - Haroun, Emran Shaeban Al-Hadi; GarGouri, llhem (Journal of Ecohumanism, 2025)
This paper sought to estimate The study mainly aimed to analyze the role of economic policies implemented by Libya, and to measure the effectiveness of these economic policies in achieving economic diversification in Libya during the period (1990-2023). To test the effectiveness of economic policies in Libya, the study relied on the inductive approach (analytical tool and descriptive tool), and also relied on the standard approach, the autoregressive distributed lag model (ARDL). The study reached a set of results at the analytical level, the most important of which is that the main reason and the biggest challenge for not achieving economic diversification in Libya is the primary reliance on oil, which constitutes a single growth model.